Incidence of Postsuppression Virologic Rebound in Perinatally HIV-Infected Asian Adolescents on Stable Combination Antiretroviral Therapy - Sudjaritruk T. (2017)
© 2017 Society for Adolescent Health and Medicine Purpose To assess the incidence and predictors of postsuppression virologic rebound (VR) among adolescents on stable combination antiretroviral therapy in Asia. Methods Perinatally HIV-infected Asian adolescents (10–19 years) with documented virologic suppression (two consecutive viral loads [VLs] < 400 copies/mL ≥6 months apart) were included. Baseline was the date of the first VL < 400 copies/mL at age ≥10 years or the 10th birthday for those with prior suppression. Cox proportional hazards models were used to identify predictors of postsuppression VR (VL > 1,000 copies/mL). Results Of 1,379 eligible adolescents, 47% were males. At baseline, 22% were receiving protease inhibitor–containing regimens; median CD4 cell count (interquartile range [IQR]) was 685 (448–937) cells/mm 3 ; 2% had preadolescent virologic failure (VF) before subsequent suppression. During adolescence, 180 individuals (13%) experienced postsuppression VR at a rate of 3.4 (95% confidence interval: 2.9–3.9) per 100 person-years, which was consistent over time. Median time to VR during adolescence (IQR) was 3.3 (2.1–4.8) years. Wasting (weight-for-age z-score < −2.5), being raised by grandparents, receiving second-line protease inhibitor–based regimens, starting combination antiretroviral therapy after 2005, and having preadolescent VF were independent predictors of adolescent VR. At VR, median age, CD4 cell count, and VL (IQR) were 14.8 (13.2–16.4) years, 507 (325–723) cells/mm 3 , and 4.1 (3.5–4.7) log 10 copies/mL, respectively. Conclusions A modest and consistent incidence of postsuppression VR was documented during adolescence in our cohort. Having poor weight, receiving second-line regimens, and prior VF were associated with an increased VR rate. Adolescents at higher risk of VR may benefit from more intensive VL monitoring to enhance adherence management.